PEER-TO-PEER LENDING REGULATORY FRAMEWORK IMPACTS ON MSMES FINANCING IN INDONESIA - Alwi, Abdurrahman Faris; Putra, Araya Anggara; Hutami, Haninda Saras; Andriany, Lia Evanty; Hanindya, Yoda Rifky (PEOPLE: International Journal of Social Sciences, 2021)
Micro, Small, and Medium Enterprises (MSMEs) contribute approximately 60% to Indonesian Gross Domestic Product (GDP). However, they struggle to obtain access in financing through traditional means, such as bank loans, due to weak credit ratings. For this reason, Peer-to-Peer (P2P) Lending exist as a viable financing alternative. Correspondingly, the Financial Services Authority (FSA) has taken a rapid measure to accommodate the growth of P2P Lending through FSA Regulation Number 77/POJK.01/2016 concerning Information Technology-Based Lending Services. However, no research analyzed the impact of the P2P Lending regulatory framework on MSMEs financing. This paper examines and analyzes the norms within the Regulation with a combination of empirical and normative approaches. First, this paper found that the purpose of P2P Lending Regulatory Framework is to promote access to financing for MSMEs. Second, P2P Lending Regulatory Framework has a crucial role in activating the digital economy ecosystem for MSMEs. In conclusion, this paper suggests that the law has a role in utilizing the potential of new tech by providing legal certainty.